The Macro-Physics of the Quark-Nova: Astrophysical Implications - Rachid Ouyed (Universe, 2022)
A quark-nova is a hypothetical stellar evolution branch where a neutron star converts explosively into a quark star. Here, we discuss the intimate coupling between the micro-physics and macro-physics of the quark-nova and provide a prescription for how to couple the Burn-UD code to the stellar evolution code in order to simulate neutron-star-to-quark-star burning at stellar scales and estimate the resulting energy release and ejecta. Once formed, the thermal evolution of the proto-quark star follows. We found much higher peak neutrino luminosities (>10<semantics>55</semantics> erg/s) and a higher energy neutrino (i.e., harder) spectrum than previous stellar evolution studies of proto-neutron stars. We derived the neutrino counts that observatories such as Super-Kamiokande-III and Halo-II should expect and suggest how these can differentiate between a supernova and a quark-nova. Due to the high peak neutrino luminosities, neutrino pair annihilation can deposit as much as <semantics>1052</semantics> ergs in kinetic energy in the matter overlaying the neutrinosphere, yielding relativistic quark-nova ejecta. We show how the quark-nova could help us understand many still enigmatic high-energy astrophysical transients, such as super-luminous supernovae, gamma-ray bursts and fast radio bursts.